(untitled) (Journal of Applied Oral Science, 2022)
High viscous glass ionomer cement (GIC) has gained popularity as a restorative material; however, high wear is pointed as one of the major drawbacks of this material. Protective surface coatings were developed to protect GIC from water contamination with the additional advantage of occluding any surface cracks or porosities commonly found in this material, possibly resulting in an increased wear resistance of the restorations. Objective: The objective of this study was to investigate the clinical wear of GIC approximal restorations in primary molars protected either with a nanofilled self-adhesive light-cured protective coating (NPC) or with petroleum jelly. Material and Methods: Approximal caries lesions in primary molars from 32 schoolchildren previously enrolled in another clinical trial were included in this investigation. GIC restorations were performed according to the Atraumatic Restorative Treatment approach and protected with either petroleum jelly or a NPC. Impressions of the restored hemiarch were done after 1 day and 6, 12, 24 and 36 months. The impressions were scanned in a 3-D appliance and the obtained images were superimposed using an appropriate computer software. Two-way ANOVA for repeated measures and Tukey's post-hoc test were used to analyze the wear of restorations (α=5%). Results: A significant difference was found between the two groups, with a wear protection offered by the application of a NPC. Conclusion: These results suggest that the application of a NPC has a protective effect on the clinical wear of approximal GIC restorations in primary teeth.